Are Circulating Monocytes as Microglia Orthologues Appropriate Biomarker Targets for Neuronal Diseases? (Supplementry Table) - Schmitz, Gerd; Leuthauser-Jaschinski, Kerstin; Orso, Evelyn (Central Nervous System Agents in Medicinal Chemistry, 2009)
Microglial cells, in contrast to other central nervous system cell types such as neurons and macroglia, are of myeloid origin. They constitute the immune cells of the brain and are involved in neuroinflammatory and neurodegenerative processes. Moreover, diseases of the central nervous system with an inflammatory component are characterized by the migration of bone marrow-derived monocytes into the brain where they differentiate into microglia, the “tissue macrophages” of the nervous system, bearing a therapeutic potential for certain diseases by transplantation of bone marrow- derived hematopoietic stem and progenitor cells. Due to their common origin, microglial cells and monocytes/ macrophages share expression of many surface receptors and signalling proteins. Moreover, there is overlap in the expression of many genes related to Alzheimer's disease. Activation of resident and blood-derived microglia in diseases of the central nervous system can be both beneficial, e.g. by degradation of protein aggregates, and detrimental, e.g. by secretion of neurotoxic factors. This review summarizes the current knowledge about the role of microglia in neurodegenerative diseases with a focus on Alzheimer's disease. Moreover, we present data how neuroinflammation is reflected by cellular changes in peripheral blood enabling the use of blood monocytes/macrophages for diagnosis, therapeutic target finding and outcome monitoring of neurodegenerative disorders. In summary, blood monocytes as microglia orthologues are an important model system to study the role of microglia in the pathogenesis of neurodegenerative diseases. They are suitable biomarker targets for diagnosis and prognosis and maybe also therapy of central nervous system disease.
Keywords: neuroinflammation